2021
DOI: 10.1098/rspb.2021.0693
|View full text |Cite
|
Sign up to set email alerts
|

The utility of genomic prediction models in evolutionary genetics

Abstract: Variation in complex traits is the result of contributions from many loci of small effect. Based on this principle, genomic prediction methods are used to make predictions of breeding value for an individual using genome-wide molecular markers. In breeding, genomic prediction models have been used in plant and animal breeding for almost two decades to increase rates of genetic improvement and reduce the length of artificial selection experiments. However, evolutionary genomics studies have been slow to incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 98 publications
(185 reference statements)
0
31
0
Order By: Relevance
“…Our data have the potential to determine individual breeding values, but this can be extended to the population level, with broader evolutionary and ecological implications. Estimating a genotype value and its frequency in a population could make it possible to predict how the population will respond to a future environmental event in respect to the phenotypic trait in question ( Hunter et al 2021 ; McGaugh et al 2021 ). This can be an important tool in the restocking of heavily affected populations, either by climatic change or by overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…Our data have the potential to determine individual breeding values, but this can be extended to the population level, with broader evolutionary and ecological implications. Estimating a genotype value and its frequency in a population could make it possible to predict how the population will respond to a future environmental event in respect to the phenotypic trait in question ( Hunter et al 2021 ; McGaugh et al 2021 ). This can be an important tool in the restocking of heavily affected populations, either by climatic change or by overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed a shift in GEBVs for adult weight in a 35 year data set for Soay sheep, though phenotypic body weight decreased over this time span 20 . Genomic prediction approaches have a wide future applicability in evolutionary studies 21 .…”
Section: Main Textmentioning
confidence: 99%
“…A recent study showed a shift in GEBVs for adult weight in a 35 year data set for Soay sheep, though phenotypic body weight decreased over this time span 20 . Genomic prediction approaches have a wide future applicability in evolutionary studies 21 The action of natural selection in the wild for increased health of European ash under ash dieback is good news, but whether the rate of change will be sufficient for evolutionary rescue to occur 15 , and whether its end point will be a fully resistant tree, is as yet unknown. The population we studied is fixed for alleles associated with high susceptibility at more than 900 loci; at these loci gene flow from other populations will be essential to introduce beneficial alleles.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic prediction [22], is a tool widely used in animal and plant breeding to estimate quantitative genetic parameters from marker data. More recently, genomic prediction has started to become adopted by researchers working on wild populations [23][24][25][26]. It works by exploiting the fact that when marker density is sufficiently high, some typed SNP markers are in linkage disequilibrium (LD) with unknown causal loci, and the contribution of each SNP (and the unknown loci it tags) to phenotypic variation can be estimated.…”
Section: Introductionmentioning
confidence: 99%